2019
DOI: 10.1111/irv.12639
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific incidence rates and risk factors for respiratory syncytial virus‐associated lower respiratory tract illness in cohort children under 5 years old in the Philippines

Abstract: Background Respiratory syncytial virus (RSV) is one of the main viral causes of lower respiratory tract illness (LRTI), especially in young children. RSV vaccines, including maternal and infant vaccines, are under development; however, more epidemiological studies are needed to develop effective vaccination strategies. Objectives To estimate detailed age‐specific incidence rates and severity of RSV‐associated LRTI (RSV‐LRTI) using data from a community‐based prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 46 publications
5
18
0
Order By: Relevance
“…Excellent surveillance across the Philippines consistently shows RSV ranking as one of the top two most commonly detected respiratory viruses each year, and as the leading cause of hospitalization among infants and young children [ 25 , 26 , 27 , 37 , 38 , 39 , 40 ]. Furuse et al found that nearly 24% of all RSV-infected children visit a medical facility during their infection, with 2% requiring hospitalization [ 38 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent surveillance across the Philippines consistently shows RSV ranking as one of the top two most commonly detected respiratory viruses each year, and as the leading cause of hospitalization among infants and young children [ 25 , 26 , 27 , 37 , 38 , 39 , 40 ]. Furuse et al found that nearly 24% of all RSV-infected children visit a medical facility during their infection, with 2% requiring hospitalization [ 38 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
“…Reported RSV positivity rates range between 12 and 27% by location, but the highest rates of detection and incidence of severe disease are consistently seen among children less than 2 years of age [ 25 , 26 , 27 , 37 , 38 ]. In addition to young age, other risk factors for the development of severe RSV included a lower educational level of caregivers and underlying malnutrition [ 26 , 39 ]. Like other parts of the world, transmission of RSV infection within households is well documented.…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
“…However, questions still remain regarding the optimal approach for RSV prophylaxis with palivizumab, and the need for additional epidemiological data regarding the incidence of RSV hospitalizations has been identified . The incidence of ARI‐ and RSV‐associated hospitalizations varies in different countries . This could be the result of diverse factors, including social conditions, environmental factors, or healthcare systems.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The incidence of ARI-and RSV-associated hospitalizations varies in different countries. [13][14][15][16] This could be the result of diverse factors, including social conditions, environmental factors, or healthcare systems. The incidence of severe RSVassociated infections in preterm infants in Mexico has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…However, this revision did not deal with the problem of underdiagnosis of obstructive airway disease. Only a few studies have analysed the impact of its implementation, especially in Southeast Asia [14][15][16][17].…”
Section: Pneumonia: Major Killer In Children Worldwidementioning
confidence: 99%